PENGARUH SOCIAL MEDIA MARKETING, CONTENT MARKETING, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE SAMSUNG DAN IPHONE PADA MAHASISWA UNIVERSITAS DI SEMARANG - Ahmada, Rikza Alby; Putra, Febrianur Ibnu Fitroh Sukono (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
Samsung and iPhone are popular brands in Indonesia's smartphone market, attracting many users. Nowadays, smartphones serve not only for communication but also as tools for digital marketing. This study focuses on examining how social media marketing, content marketing, and brand image affect the choices of university students in Semarang when it comes to buying Samsung and iPhone smartphones. We collected data from 100 students selected using a specific sampling method. We used a Likert scale questionnaire and IBM SPSS 25 for analysis. The results showed that social media marketing doesn't influence purchase decisions for Samsung and iPhone. However, content marketing and brand image significantly influence both brands. In general, these factors positively impact purchase decisions, with Samsung having a slightly higher impact compared to iPhone. There's no significant difference between the two brands. These findings can help businesses improve their marketing strategies for better targeting consumers.